Giant photoresponsivity of transfer free grown fluorographene – MoS2 heterostructured ultra-stable transistors. (November 2021) - Sharma, Rahul; Sharma, Prince; Sahoo, Krishna Rani; Sankar, Soumya; Awana, V.P.S.; Kumar, Mahesh; Narayanan, Tharangattu N.
Graphical abstract: Abstract: Development of metal dichalcogenides based air and water stable opto-electronic devices is a bottleneck in their commercial implementation. Here we address this issue by the direct catalyst-free deposition of fluorographene (FG) protective layer over monolayer MoS2 (MS), where such an atomic interface is found to be providing enormous photoresponse and chemical stability to the device. Electric field modulated (ionic liquid (IL) electrolyte based top-gated) photodetectors are developed with MS only and FG-MS heterostructure, where the MS photodetector has the responsivity of ~1.3 A/W (with V GS  = 0 V while unstable with IL gating) while that of FG-MS is ~2000 A/W (with V GS  = 0 V and ~8000 A/W with V GS  = 1.5 V, and the detectivity ~10 13 ). This giant photoresponse of the FG-MS is validated with the help of ultrafast transient absorption spectroscopy assisted charge carrier dynamics studies at different temperatures. The broad optical response (350–850 nm) of the FG-MS is found to be intact not only in IL based gating but also after exposing in water for a month or heat treated in air at 200 °C. Interfacing and capping with FG, developed via the direct growth method, are found to be ideal for realizing high shelf-life and good responsivity photodetectors and solar cells of several other monolayer TMDs too, while available for wafer-scale manufacture.